Phenolics from Castanea sativa leaves and their effects on UVB-induced damage. Issue 10 (19th May 2018) - Cerulli, Antonietta; Masullo, Milena; Mari, Angela; Balato, Anna; Filosa, Rosanna; Lembo, Serena; Napolitano, Assunta; Piacente, Sonia
Abstract: The phytochemical investigation of the methanol extract of the leaves of Castanea sativa Mill., source of the Italian PGI (Protected Geographical Indication) product 'Marrone di Roccadaspide' (Campania region) afforded as main compounds crenatin (1 ), chestanin (2 ), gallic acid (3 ), cretanin (4 ), 5- O - p -coumaroylquinic acid (5 ), p -methylgallic acid (6 ) and quercetin-3- O -glucoside (7 ). To quantify the isolated compounds a LC-ESI(QqQ)MS method working with a very sensitive and selective mass tandem experiment called Multiple Reaction Monitoring (MRM) has been developed. Moreover the antioxidant capacity by TEAC assay and the ability of compounds1 –7 to protect HaCaT human keratinocytes from UVB-induced damage has been investigated. Abstract :